2016
DOI: 10.1103/physrevc.93.034623
|View full text |Cite
|
Sign up to set email alerts
|

Elastic scattering and breakup ofBe11on protons at26.9AMeV

Abstract: The elastic scattering and breakup of the halo nucleus 11 Be on protons at an incident energy of 26.9A MeV have been measured. The 11 Be +p elastic scattering cross sections at various energies, including the present one, are systematically analyzed with the Chapel Hill 89 (CH89) and Koning-Delaroche (KD) global optical model potentials (OMPs), and the corresponding normalization factors are obtained. An extended version of the continuum-discretized coupled-channels (XCDCC) formalism, including dynamic core ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…As in previous works [15,19,34], the 11 Be structure is described with the Hamiltonian of Ref. [35] (model Be12-b), which consists of a Woods-Saxon central part (R = 2.483 fm, a = 0.65 fm) and a parity-dependent strength (V c = −54.24 MeV for positive-parity states and V c = −49.67 MeV for negative-parity ones).…”
Section: Application To 11 Be Reactionsmentioning
confidence: 99%
“…As in previous works [15,19,34], the 11 Be structure is described with the Hamiltonian of Ref. [35] (model Be12-b), which consists of a Woods-Saxon central part (R = 2.483 fm, a = 0.65 fm) and a parity-dependent strength (V c = −54.24 MeV for positive-parity states and V c = −49.67 MeV for negative-parity ones).…”
Section: Application To 11 Be Reactionsmentioning
confidence: 99%
“…However, there is evidence that this approximate model is not always accurate [11][12][13]. For example, recent calculations [14] have shown that, in collisions of 11 Be with light targets, the explicit inclusion of the DCE mechanism gives rise to a sizable increase of the breakup cross section. This is particularly important for excitation energies around the low-lying 3/2 + resonance, where the effect is enhanced due to the dominant 10 Be(2 + ) configuration for this resonance.…”
mentioning
confidence: 99%
“…Two parallel-plate avalanche counters (PPAC) placed upstream of the target provided beam tracking information, with the resolution of incident angles and hitting positions on the target less than 0.3 • and 2.0 mm, respectively. Elastic scattering of 11 Be from protons or deuterons was measured by using a (CH 2 ) n (4.00 mg/cm 2 ) or a (CD 2 ) n (4.00 mg/cm 2 ) target, respectively, with the C-target (12.58 mg/cm 2 ) providing the background subtraction [29,30]. The same (CD 2 ) n target was used for the 11 Be(d, p) 12 Be reaction.…”
Section: Methodsmentioning
confidence: 99%
“…Only the elastic scattering data are shown here, and the data from breakup channels were detailed in Refs. [29,30]. The elastic scattering or breakup reaction channels were separated by the coincidence of 11 Be or 10 Be measured by the TELE0 and light particles (protons/deuterons) detected by the TELE1.…”
Section: A Elastic Scattering Reactionmentioning
confidence: 99%
See 1 more Smart Citation